Explanatory models of executive functions - Echavarría, Luis Miguel (2017)
Executive functions (FE) are considered as a theoretical construct, referring to the capacity we have as human beings to plan, organize, inhibit, monitor our behavior and be flexible in the face of novel situations. However, this definition is not the only one, since many authors conceptualize it in different ways and this means that different models are presented that try to explain the nature of such functions; However, a consensus has not yet been reached.Therefore, the present work, brings to light those models that seek to explain executive functions in all their magnitude and complexity, finding from anatomical positions to statistical trends or to consider how they develop the FE in the stages of development, the same that were Raised in order to have a better understanding of them.